Identification and Molecular Phylogeny of Morphologically of the Medicinal Plant Calligonum L’Herit - Abdullah Alaklabi (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The rare gem species of Calligonum comosum contains highly therapeutic compounds collected from Al-Qassim region, Saudi Arabia. It has various biological properties that used for antimicrobial, antioxidant, anti-inflammatory, anti-gastric ulcer, anti-hyperglycemic, abdominal ailments as well as against toothache. Methods: Calligonum L. (Polygonaceae) genus consists of 158 species dispersed in Asia, Africa and Middle East. Remarkably a very few researches found molecular phylogeny of Calligonum comosum, it is one of the significant medicinal plants used in various herbal preparations and most commonly adulterated by the morphologically similar species, viz C. ebinuricum. The species C. junceum, C. Colubrinum and C. arborescens is often misidentified as Calligonum comosum hence, thereby accurate identification of this medicinal herb are very crucial which ensures the drug effectively as well as biosafety. Thus, in this study, DNA barcoding tool was used for precise identification, its conservation development and differentiating from analogous species of C. comosum. Results: The barcode genes like nuclear internal transcribed spacer region ITS2, the chloroplast plastid gene matK and rbcL were used for phylogenetic analysis of Calligonum species. From the sequence alignment the nuclear internal transcribed spacer ITS2 regions shows 9.5% of polymorphic sites, indicates higher range of transition/transversion (ts/tv) ratio and percentage of variation which aids to discriminate Calligonum comosum from its closely related species. Conclusion: The present phylogeny proves that the nuclear internal transcribed spacer ITS2 region distinguishes the closely related species of Calligonum comosum from its morphologically similar species.